دور إدارة الجمارك في متابعة الجريمة الجمركية - مفيدة, طبة (جامعة الوادي - University eloued, 2022)
وفي ختام هذه المذكرة المعنونة ب: ( دور إدارة الجمارك في متابعة الجريمة الجمركية) المتطرق فيها إلى جانبين جانب نظري وآخر موضوعي في الجانب النظري تمت فيه دراسة كل من القواعد الموضوعية ف يالجريمة الجمركية المختلفة عن المبادىء العامة عن الجرائم الأخرى ضف إلى هذا المركز القانوني لإدارة الجمارك من حيث التقسيم والمهام والوسائل. في الجانب الموضوعي والذي هو لب المذكرة تطرقت فيه إلى دور إدارة الجمارك في متابعة الجريمة الجمركية للأساليب المخولة لأعوان الجمارك وكذلك أساليب قانونية أخرى ليتم وضع حد لهاته الجرائم بأجراء المصالحة الجمركية أو بتنفيذ العقوبة At the end of this note entitled: ( The role of the customs administration in the follow - up of Customs crime), it touched on two aspects, one theoretical and one objective In the theoretical aspect, each of the substantive rules of the customs crime was studied, which differs from the general principles of other crimes. add to this the legal status of the customs administration in terms of division, tasks and Means. On the substantive side, which is the core of the memorandum, I touched upon the role of the customs administration in following up the customs crime with the methods authorized to customs agents, as well as other legal methods to put an end to these crimes by conducting customs reconciliation or executing the penalty
مذكرة ماستر
Keywords: إدارة الجمارك، الجريمة الجمركية، الاختصاص القضائي; Customs Administration, Customs Crime, Jurisdiction